Education Trend Analysis Use of Physical Education Learning Models: Systematic Literature Review - Haris, Iyan Nurdiyan; Yulianto, Ari Gana; Riyanto, Aris; Rosti (STKIP Paasundan Press, 2024)
The aim of this systematic literature review is to examine the scientific literature pertaining to research trends and outcomes associated with the utilization of physical education learning models. The study employs Harzing's Publish or Perish application to navigate the Google Scholar database over the past decade, selecting articles that offer insights into the application of physical education learning models. The research methodology involves a systematic literature review, utilizing the prism flow diagram for article identification during the filtering and data extraction phases. Out of the 361 initially downloaded articles, a final set of 88 articles undergoes inclusion and exclusion screening based on specific criteria, followed by thorough analysis. The findings of the review align with systematic analyses of literature reviews, revealing prevalent trends in the utilization of various physical education learning models. Notably, cooperative learning emerges as the primary model explored consistently over the years. The results highlight that implementing physical learning models in primary and secondary schools yields positive effects on students. The incorporation of innovative and pertinent physical learning models is shown to enhance student participation, improve learning outcomes, foster better health and physical well-being, boost motivation, and enhance student engagement in the learning process.